2018
DOI: 10.3892/etm.2018.6860
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid ameliorates learning and memory impairment in APP/PS1 transgenic mice via inhibition of β‑amyloid production and tau hyperphosphorylation

Abstract: β-amyloid (Aβ) aggregation and tau hyperphosphorylation are considered to be the primary pathological hallmarks of Alzheimer's disease (AD). Targeted inhibition of these pathological processes may provide effective treatments for AD. Accumulating evidence has demonstrated that ellagic acid (EA) exerts neuroprotective effects in several diseases. The present study investigated the effects of EA on AD-associated learning and memory deficits on APP/PS1 double transgenic mice and the underlying mechanisms. APP/PS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Notably, it has been demonstrated that different lengths of Tau may be degraded through different autophagic pathways; the full-length Tau is preferentially degraded through macroautophagy, whereas truncated Tau (for one, TauRdΔK280) is cleared through chaperone-mediated autophagy (30). Although the APP/PS1/Tau tri-transgenic Ad mouse model is an ideal model with which to study the pathology of Aβ and Tau, the tau-induced pathology in the APP/PS1 double-transgenic Ad mouse model was also found in our previous study and in other reports (31)(32)(33). This study examined the effects of rapamycin on Tau clearance.…”
Section: Discussionsupporting
confidence: 57%
“…Notably, it has been demonstrated that different lengths of Tau may be degraded through different autophagic pathways; the full-length Tau is preferentially degraded through macroautophagy, whereas truncated Tau (for one, TauRdΔK280) is cleared through chaperone-mediated autophagy (30). Although the APP/PS1/Tau tri-transgenic Ad mouse model is an ideal model with which to study the pathology of Aβ and Tau, the tau-induced pathology in the APP/PS1 double-transgenic Ad mouse model was also found in our previous study and in other reports (31)(32)(33). This study examined the effects of rapamycin on Tau clearance.…”
Section: Discussionsupporting
confidence: 57%
“…Ellagic acid, which belongs to hydroxybenzoic acids, has been shown to exert neuroprotective effects by modulating neuroinflammation is a promising constituent for improving cognitive impairment [ 55 ] and alleviating memory impairment [ 56 ]. The neuroprotective activity of ellagic acid has been also validated in APP/PS1 mice, a validated transgenic animal model of Alzheimer’s disease, where it prevents neuronal apoptosis in the hippocampus and rescues memory deficits through the inhibition of beta-amyloid production and tau hyperphosphorylation [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that EA inhibits human platelet activation upon stimulation with hydrogen peroxide, by inhibiting phosphorylation events of MAPK p38, Akt, phospholipase C, and protein kinase C [ 49 ]. In addition, EA was reported to inhibit tau phosphorylation, one of the prime suspects involved in AD pathology, leading to learning and memory improvements in a mice model of AD [ 50 ]. In a more recent study, EA revealed a strong binding affinity for sphingosine kinase 1, repressing phosphorylation by restricting ATP accessibility [ 51 ].…”
Section: Discussionmentioning
confidence: 99%